Educational resources accessible on the tele-rehabilitation platform - Acosta-Vargas, Patricia (2019)
his research is part of a telemedicine platform project to guide and accompany the patient online, during rehabilitation after total or partial hip replacement surgery. The study proposes to apply the Accessibility Guidelines for educational content in accordance with the Web Accessibility Initiative (WAI) accessibility guidelines. The main functionalities of the tele-rehabilitation platform involve the execution of rehabilitation movements, remote communication with health professionals, and therapeutic education of the patient during the recovery process. This article discusses the guidelines that the teaching-learning resources for elderly patients must meet to generate inclusive and easily accessible resources. The present study takes into consideration specific parameters relevant to the design of educational resources, with the aim of providing more accessible and inclusive educational guidelines for elderly patients